(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
اعتماداً على منهجية حساب الخصائص الترموديناميكية الحرارية للبلورات عند درجات الحرارة العالية تم في هذا العمل حساب الخصائص الترموديناميكية الحرارية لبلورة الأرغون على امتداد ثمانية منحنيات إيزوحرارية تمتد من 60K إلى 300K عند حجم مولي تتراوح قيمته بين 15 cm3/mol وحتى قيمته الموافقة لمنحنيات التوازن التجريبية مع الطورين الغازي والسائل وضمن حدود تطبيق التقريب شبه التقليدي. و في هذه الحسابات تم استخدام كمون لينارد جونز لتمثيل قوى التأثير المتبادل الثنائية وكمون أكسيلرود-تيلير لتمثيل قوى التأثير المتبادل الثلاثية. ولقد تبين بنتيجة هذه الدراسة إمكانية تمثيل الضغط في هذا المجال الواسع من مخطط الحالة بتابع خطي لدرجة الحرارة أما معامل المرونة الحراري BT فلا يتبع عملياً لدرجة الحرارة عند حجم ثابت. ويمكن تمثيل تبعيته للحجم (V) BT في حالة الانضغاطات غير الشديدة بتابعٍ أسيٍ متوافقٍ مع النتائج التجريبية. On the basis of the methodology for calculating the thermal thermodynamic properties of crystals, thermal thermodynamic properties of crystalline argon Ar are calculated in this work along eight isothermal curves, expanded from 60 K up to 300K at molar volume expanded from 15cm3/mol up to its value, corresponded experimental equilibrium curves with gaseous and liquid phases within the framework of quasi-classical approximation. The inter-atomic forces are assumed, in these calculations, to be described using Lennard-Jones 12:6 pair potentials in conjunction with the Axilrod-Teller three-body potential. It was found that the pressure, over this wide range of state diagram, could be approximated as a linear function of temperature while the isothermal bulk modulus BT does not depend on temperature when volume is constant. At the same time, the dependency of bulk modulus BT on volume BT (V) could be approximated exponentially when the compression is not very high. This finding coincides well with the experimental results.